2020
DOI: 10.1088/1757-899x/935/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of furfurylated mangium (Acacia mangium Willd.) and pine (Pinus merkusii Jungh et de Vriese) woods

Abstract: Wood from plantation forest contains a lot of sapwood and juvenile wood which has inferior in physical properties. Furfurylation could improve the properties through a reaction between Furfuryl Alcohol (FA) with a hydroxyl group of wood components. The purpose of the study was to improve the physical properties of mangium (Acacia mangium Willd.) and pine (Pinus merkusii Jungh et de Vriese) woods. The wood specimens for physical properties was prepared according to the ASTM D 143-94. They were vacuumed at 600 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Increasing the concentration to 20% caused the WPG of FW54 and PW40 to reach ~54% and ~41%, respectively, which indicated that the WPG of Chinese fir was generally higher than that of poplar. Mulyosari et al demonstrated that the WPG of furfurylated wood was related to differences in softwood and hardwood anatomical structure [34]. It has also been demonstrated that hardwood is easier to impregnate treatment than softwood [35,36].…”
Section: Analysis Of the Wpg And Bc Of Furfurylated Woodmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the concentration to 20% caused the WPG of FW54 and PW40 to reach ~54% and ~41%, respectively, which indicated that the WPG of Chinese fir was generally higher than that of poplar. Mulyosari et al demonstrated that the WPG of furfurylated wood was related to differences in softwood and hardwood anatomical structure [34]. It has also been demonstrated that hardwood is easier to impregnate treatment than softwood [35,36].…”
Section: Analysis Of the Wpg And Bc Of Furfurylated Woodmentioning
confidence: 99%
“…Svensson et al found that the release of organic compounds from wood in contact with water is related to its species and anatomical structure [41]. Numerous studies have demonstrated the existence of a chemical reaction between furfuryl alcohol and lignin [34,42], which leads to a tighter bonding and enhanced structural stability. Therefore, the differences in the leachability and M L of poplar and Chinese may be due to the higher pit aspiration and lignin content of Chinese fir wood cells, which makes FA resin more likely to retain and form macromolecules.…”
Section: Analysis Of Leachatementioning
confidence: 99%